2020
DOI: 10.3390/cancers12102966
|View full text |Cite
|
Sign up to set email alerts
|

High PD-L1/CD274 Expression of Monocytes and Blood Dendritic Cells Is a Risk Factor in Lung Cancer Patients Undergoing Treatment with PD1 Inhibitor Therapy

Abstract: The aim of this study was to investigate the expression of the coinhibitory molecule PD-L1/CD274 in monocytes and dendritic cells (DC) in the blood of lung cancer patients undergoing PD1 inhibitor therapy and to correlate data with patient’s outcome. PD-L1/CD274 expression of monocytes, CD1c+ myeloid DC (mDC) and CD303+ plasmacytoid DC (pDC) was determined by flow cytometry in peripheral blood at immunotherapy onset. The predictive value of the PD-L1/CD274-expression data was determined by patients’ survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Importantly, recent studies have shown that blocking PD-L1 on DCs improves DC function and leads to enhanced anticancer T cell immunity [ 57 , 58 ]. Furthermore, the expression of PD-L1 on pDCs has also been associated with the induction of tolerogenic immune responses in different experimental settings [ 59 , 60 ] as well as to bad prognosis in cancer patients [ 61 ]. This argues in favor of a role for the upregulation of PD-L1 on pDCs in the development of an impaired antiviral immune response that we observed in NK cell-depleted, infected/treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent studies have shown that blocking PD-L1 on DCs improves DC function and leads to enhanced anticancer T cell immunity [ 57 , 58 ]. Furthermore, the expression of PD-L1 on pDCs has also been associated with the induction of tolerogenic immune responses in different experimental settings [ 59 , 60 ] as well as to bad prognosis in cancer patients [ 61 ]. This argues in favor of a role for the upregulation of PD-L1 on pDCs in the development of an impaired antiviral immune response that we observed in NK cell-depleted, infected/treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, a DC gene signature was strongly associated with improved patients’ OS in NSCLC patients undergoing Atezolizumab therapy (PD-L1 blockade) [ 55 ]. DC counts and their expression of coinhibitory molecules, such as PD-L1, can affect therapy response and patients’ survival; patients undergoing ICI monotherapy and exhibiting a higher PD-L1/CD274 expression of DC subtypes and monocytes, respectively, showed a significantly poorer survival [ 56 ]. Understanding and modulating DC counts and functional activity might help to improve the efficacy of T cell-centric immunotherapies in tumor patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the clinical significance of IDO1 expression in monocytes of the peripheral blood of cancer patients has not been reported yet. For PD-L1 expression by monocytes, however, a study in lung cancer patients receiving anti-PD-1 demonstrated that PD-L1 expression was higher on HLA-DR hi monocytes and correlated with low PFS ( 60 ).…”
Section: Discussionmentioning
confidence: 99%